2021
DOI: 10.3389/fonc.2020.588533
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Emodin Interferes With AKT1-Mediated DNA Damage and Decreases Resistance of Breast Cancer Cells to Doxorubicin

Abstract: Doxorubicin (DOX) is a cytotoxic drug used for the treatment of breast cancer (BC). However, the rapid emergence of resistance toward doxorubicin threatens its clinical application, thus the need for combination therapy. Here, we interrogate the role of Emodin, a chemical compound with tumor inhibitory properties, in the resistance of BC to Doxorubicin. We first evaluated the efficacy of Emodin in the treatment of BC cells. We then used γH2A to examine doxorubicin-induced DNA damage in BC cells, with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Li et al . reported that DOX combined with emodin can improve the sensitivity of MDA-MB-231 and MCF-7 cells to chemotherapy, and the mechanism is closely related to increasing γH2A in cancer cells and regulating AKT1-mediated DNA damage 125 .…”
Section: Anticancer Effects Of Emodinmentioning
confidence: 99%
“…Li et al . reported that DOX combined with emodin can improve the sensitivity of MDA-MB-231 and MCF-7 cells to chemotherapy, and the mechanism is closely related to increasing γH2A in cancer cells and regulating AKT1-mediated DNA damage 125 .…”
Section: Anticancer Effects Of Emodinmentioning
confidence: 99%
“…Emodin significantly augmented cells in the G1/G0 phase and reduced cells in the G2/M and S phases in the A549 cell line. In addition, while decreasing the expression of cyclin A and cyclin B in the same cell line, it increased the levels of cyclin C, cyclin D, and cyclin E. These cyclin proteins are not altered by emodin exposure when HAS2 is deactivated, suggesting that emodin regulates HAS2, affecting the cell cycle [ 80 ].…”
Section: Anticancer Activity Of Emodinmentioning
confidence: 99%
“…Combination treatment increased the γH2Ax expression and the DNA damage and resulted in decreased expression of the AKT1, p53, PARP1, RAD51, and XRCC1 signaling pathway. According to the in vitro test results, it was determined that tumor size, weight, and KI67 expression decreased [ 80 ]. However, in contrast to these studies, a different combined therapy study showed that emodin reduced the effectiveness of tamoxifen in ZR-75-1 and MCF-7 cells.…”
Section: Anticancer Activity Of Emodinmentioning
confidence: 99%
“…One such method is administration of a cytostatic drug along with a biological substance to support its activity. For example, combination therapy using emodin and doxorubicin sensitize breast cancer cells to doxorubicin by inhibition of proliferation in the DNA damage pathway (decreasing the levels of X-ray repair cross complementing 1 (XRCC1), poly(ADP-ribose) polymerase 1 (PARP1) and RAD51 proteins) and by downregulation of the expression of AKT1 and enhancement of the expression of p53 [67].…”
Section: Effects Of Emodin On the Activity Of Drugsmentioning
confidence: 99%